ANALISIS KONFLIK AGRARIA (STUDI KASUS DALAM IZIN PENAMBANGAN BAHAN GALIAN GOLONGAN C (PASIR DAN KERIKIL) DI DESA TERANTANG KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2012) - Faldi, Ibnu; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study describes the process of conflict and handling conflicts that occurred in the village Terantang Mining District of Kampar. Where the object is the cause of this conflict is the presence of volatile permission granted by government authorities against the mining business, located in the village of Terantang.Sementara that, from the beginning of mining has been rejected by indigenous peoples Terantang village, by reason of damaging the environment and mining areas is still included into the traditional lands of indigenous peoples Terantang.Sementara village, in providing the appropriate government permission in violation of the procedure. Where it should be before the permit is issued must first be approved by the local community and should consider the environmental kersakan will happen. However, it is not done, so this is what makes this volatile conflict. The method used in this study is a qualitative approach with a qualitative analysis method deskriptif.Dipilihnya this approach as a method of analysis in this study because in this study the focus I want to see is how the settlement of the conflict mineral permits in the village Terantang class C Mining District of Kampar , Keywords: agrarian, indigenous peoples and conflict.